Multi-phase Training in Virus-Like Particle Synthesis to Foster Science Self-efficacy in Students With Minimal Laboratory Experience - Macie Proctor-Roser; Marinca Faimau; Julianne Peabody; Krystal Charley; Bryce Chackerian; Naomi Lee (Bio-Protocol)
Science self-efficacy describes the confidence individuals have in their ability to accomplish specific scientific practices. Self-efficacy is one factor linked to success and persistence within STEM fields. The purpose of this protocol is to provide research laboratories with effective methods for teaching and mentoring new students in molecular biology, specifically in the synthesis of virus-like particles (VLPs) derived from bacteriophages. VLPs are multivalent nanoparticle structures that can be utilized in multiple biomedical applications, including platforms for vaccine and drug delivery. Production of bacteriophage VLPs using bacterial expression systems is feasible in most laboratory settings. However, synthesizing and characterizing VLPs can be challenging for new researchers, especially those with minimal laboratory experience or a lack of foundational knowledge in molecular biology. To address this, a multi-phase training protocol was implemented to train new students in VLP synthesis, purification, and characterization. This model was optimized for training numerous high school and undergraduate students. By implementing this multi-phase methodology, the students’ confidence in their abilities to perform specific tasks increased and likely enhanced their persistence in STEM.